Exile and restoration a study of Hebrew thought of the sixth century BC - Ackroyd, Peter R.; Hulsean lectures, 1960-1962. (London, UK SCM, 1968)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Minor Prophets -- history -- sixth century BC